Development of Laponite® hydrogels for cisplatin delivery - Duarte, Ana Sofia de Gouveia (2024)
Cancer remains a major health concern worldwide and the development of effective therapies remains a challenge. Laponite® is a synthetic nanoclay that possesses properties such as easy functionalization, degradability, and biocompatibility. More importantly, Laponite® can form strongly thixotropic gels at higher concentrations which can be explored as an avenue to drug delivery. Amongst the drugs used for cancer therapy, cisplatin, a platinum-containing metallodrug, is especially used due to its mechanism of action, which involves interference with the cells’ DNA. The main goal of this work was to formulate hydrogels composed by Laponite for the delivery of cisplatin. These gels are aimed for topical application or, eventually, for direct injection in the tumor site. As such, the preparation of Laponite hydrogels was first optimized (regarding type of liquid medium, temperature, Laponite concentration, solvent pH vs gelation time and gel consistency and transparency) and the gels were then studied to assess their ability to load (different cisplatin concentrations were assayed) and release cisplatin (at two different environmental pH values). Furthermore, the gels’ cytotoxicity was evaluated in vitro in two cell lines, A2780 (human ovarian carcinoma) and its related cell line A2780cis (resistant to cisplatin). Cytotoxicity studies were carried out using two different approaches which mainly differed regarding the type of contact between the gels and the cells (direct and non-direct). Characterization of the gels by SEM/EDS showed that cisplatin enhances cohesion within the gels. Drug release was sustained but not sensitive to pH. Additionally, in vitro studies showed that non-loaded Laponite gels promoted cells’ viability and gels containing cisplatin were cytotoxic in a concentration-dependent manner. Even though it was not possible to distinguish the two approaches used in this work regarding cytotoxicity, it was possible to conclude that Laponite hydrogels are promising platforms for cisplatin delivery.